Stories of fairies - Lester, Anna (London : Usborne Publishing Ltd, 2006)
Crystal, Lily and Poppy are three fairies in a flap. With stolen wands, flying lessons and Fairy Balls, there's never dull moment. Come to Fairyland and join in the magical fun
Shelving Location Readers Section. Fiction Book Section
Keywords: Children's fiction